KEDUDUKAN WALI NANGGROE DI ACEH - Baihaqi A Samad (Jurnal Ilmiah Peuradeun, 2014)
Law on Governing Aceh instructs is Wali Nanggroe an institution for the benefit of the people and the future of governance in Aceh. as the 'Wali' in point 1.1.7 of the Helsinki MoU and Law. No. 11/2006, must be traced to its roots in the context of the Imamate, socio-political, legal and moral. The person who bears the title "Wali" to get an important position in the social system of Islam, either because of their spiritual qualities as well as the social roles they play.This paper attempts to look at the extent to which the position of the Wali Nanggroe the application of Islamic law in Aceh. Wali Nanggroe Institution is an independent organization that is not the executive, legislative and judicial branches. "It is clear that, Wali Nanggroe no authority in politics. In Article 96 and 97 of the Act (Act) No. 11 of 2006 expressly stated that the Wali Nanggroe have a duty as an adhesive Acehnese society through custom approach and not a political institution.